Unveiling the Path to Environmental Sustainability through Energy Efficiency, Environmental Innovation, and Institutional Quality in Southeast Asian Countries - Qamruzzaman, Md; Farzana, Nusrat; Mindia, Piana Monsur (International Journal of Energy Economics and Policy, 2024)
This study examines the correlation between environmental innovation (EI), energy efficiency (EE), institutional quality (IQ), and environmental sustainability (ES) in the Southeast Asian economy from 1980 to 2019. The analysis employs both symmetric and asymmetric frameworks to provide a comprehensive understanding of the topic. The preliminary evaluation employing SHT, CSDT, and PURT indicates that the research variables demonstrate heterogeneity properties, cross-sectional dependence, and stationarity following the first difference. Moreover, the cointegration test results confirm a sustained relationship between the variables being explained and the explanatory variables in the long term. Utilizing the CS-ARDL methodology for symmetric analysis, this study reveals a positive and statistically significant correlation between the explanatory variables and environmental sustainability. This proposition posits that promoting EI, EE, and IQ can contribute to attaining the overarching objective of environmental protection. The study investigates long-term and short-run asymmetric relationships utilizing the standard Wald test, presenting definitive evidence. The presence of asymmetric coefficients reveals that positive and negative shocks in EI, EE, and IQ negatively influence environmental sustainability indicators, specifically CO2 emissions and ecological footprint. This statement suggests that the implementation of environmentally-focused innovation, the integration of clean energy, and the establishment of effective governance have the potential to bolster environmental quality through the reduction of CO2 emissions and the enhancement of ecological conditions. Regarding directional causality, the feedback hypothesis explores the causal connection between EE, IQ, and ES. The study’s findings offer valuable insights for formulating policies that will effectively guide future development endeavors in the region. In conclusion, this research highlights the importance of fostering environmental innovation, promoting energy efficiency, and enhancing institutional quality as essential measures for achieving environmental sustainability in the Southeast Asian economy.